Creating Future Agricultural Leaders Within Native Nations of Oklahoma - Jann S. Hayman (Adult Education Research Conference, 2022)
This research looks at the agricultural history and current agricultural systems of four Oklahoma-based Native nations and the College of the Muscogee Nation. The study also specifically looks at the development of future agricultural leaders.
Keywords: Native nation agriculture; Indigenous leaders; agricultural leaders